Effects of Gamma Radiation Exposure and Giving of Green Bean Sprout Extract (Phaseoulus radiatus) to Gonad Animal Fertility Rate of Mice - Feris Kamlasi; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2014)
Gamma rays is an ionizing radiation that can causes infertilities.Cell defense mechanism against free radicals are involving active compound called antioxidant. Goal of this research is aim to analyze the influence of gamma radiation and review the influence of green beansprout extract (Phaseoulus radiatus) in gonad fertility rate with threevariables there are motility, viability and abnormality of spermatozoa. Male mice divided into three groups, control (K), non-extract radiation (RNE), and radiation plus extract (R+E).Mice was treated orally by green bean sprout extract with several dose 0.2 mL kg-1 body weight, 0.4 mL kg-1 body weight, 0.6 mL kg-1 body weight, 0.8 mL kg-1 body weight, and 1.0 mL kg-1 body weight. Radiation was given by fractionation starting from 100 rad, 150 rad, 200 rad, 250 rad, and 300 rad.The result shows that increasing radiation dose can reducing gonad fertility rate and treatment of Phaseoulus radiatus extract can suppress this reduction and preserve gonad fertility rate.